Staging Subjectivity: Love and Loneliness in the Scene of Painting with Charlotte Salomon and Edvard Munch - Pollock, Griselda (Text Matters: A Journal of Literature, Theory and Culture, 2017)
This paper proposes a conversation between Charlotte Salomon (1917–43) and Edvard Munch that is premised on a reading of Charlotte Salomon’s monumental project of 784 paintings forming a single work Leben? oder Theater? (1941–42) as itself a reading of potentialities for painting, as a staging of subjectivity in the work of Edvard Munch, notably in his assembling paintings to form the Frieze of Life. Drawing on both Mieke Bal’s critical concept of “preposterous history” and my own project of “the virtual feminist museum” as a framework for tracing resonances that are never influences or descent in conventional art historical terms, this paper traces creative links between the serial paintings of these two artists across the shared thematic of loneliness and psychological extremity mediated by the legacy of Friedrich Nietzsche.